Digital tools for brownfield redevelopment: Stakeholder perspectives and opportunities. (1st January 2023) - Hammond, Ellis B.; Coulon, Frederic; Hallett, Stephen H.; Thomas, Russell; Hardy, Drew; Beriro, Darren J.
Abstract: Brownfield redevelopment is a complex process often involving a wide range of stakeholders holding differing priorities and opinions. The use of digital systems and products for decision making, modelling, and supporting discussion has been recognised throughout literature and industry. The inclusion of stakeholder preferences is an important consideration in the design and development of impactful digital tools and decision support systems. In this study, we present findings from stakeholder consultation with professionals from the UK brownfield sector with the aim of informing the design of future digital tools and systems. Our research investigates two broad themes; digitalisation and the use of digital tools across the sector; and perceptions of key brownfield challenge areas where digital tools could help better inform decision-makers. The methodology employed for this study comprises the collection of data and information using a combination of interviews and an online questionnaire. The results from these methods were evaluated both qualitatively and quantitatively. Findings reveal a disparity in levels of digital capability between stakeholder groups including between technical stakeholder types, and that cross-discipline communication of important issues may be aided by the development of carefully designed digital tools. To this end, we present seven core principles to guide the design and implementation of future digital tools for the brownfield sector. These principles are that future digital tools should be: (1) Stakeholder driven, (2) Problem centred, (3) Visual, (4) Intuitive, (5) Interactive, (6) Interoperable, and (7) Geospatial data driven. Graphical abstract: Image 1 Highlights: There is a large disparity between UK brownfield stakeholder digitalisation levels. Perceived barriers for redevelopment vary greatly between stakeholder groups. Better communication of costs, risk, and uncertainty leads to better decisions. Seven core principles for the development of brownfield digital tools are presented.